Targeting Inflation in a Dollarized Economy: The Peruvian Experience - Adrián Armas; Francisco Grippa (Inter-American Development Bank, Research Department, 2005)
This discusses the unique experience of Peru`s Central Bank with inflation targeting in an economy characterized by a high degree of financial dollarization. The paper outlines how Peru has taken financial dollarization into consideration in the design of monetary policy, then deals with monetary policy implementation and the Central Bank`s strategy for controlling financial dollarization risks. The paper concludes with analysis and lessons drawn from the Peruvian case.
Keywords: 330; Inflationssteuerung; Währungssubstitution; Geldpolitik; Peru